Development and Validation of UV/visible Spectrophotometric Method for Estimation of Piroxicam from Bulk and Formulation - Honmane, Sandip Mohan; Yadav, Kunal Rajaram; Dange, Yuvraj Dilip; Pattekari, Suraj Nijamso; Tiwari, Shradha Shivdayal; Saralaya, Mahesh Govind (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Piroxicam (PRX) is a potent anti-inflammatory medicine used both orally and topically to treat arthritis, gout, and other inflammatory disorders. Developing and testing an effective analytical technique is critical for quantitative estimations. Materials and Methods: This study provides a straightforward, exact, repeatable, accurate, and cost-effective UV-visible spectrophotometric method for quantifying PRX in bulk and formulation using Phosphate Buffer Saline (PBS) pH 7.4. In compliance with the International Conference on Harmonization (ICH) guidelines, the developed method was validated for several aspects, including robustness, specificity studies, accuracy, linearity, precision, and range. Results: PRX showed absorbance Maximum (λmax) at 354 nm in PBS pH 7.4. The value of the correlation coefficient (R2) was found to be 0.995 in the range of 2-10 μg/mL. The percent recovery of PRX was found in the range of 98.86-101.44% with less than 2 percentage Relative Standard Deviation (% RSD). The percent recovery from nanosuspension and PRX solution was found to be 99.83% and 100.6% respectively. This indicates that there was no excipient interference. Conclusion: The % RSD for every parameter was less than 2%, which indicated that the developed method was accurate, precise, specific, and suitable for the analysis of commercial samples.
Keywords: PRX; UV/visible Spectrophotometry; Nanosuspension